Scaling up UAVs for land administration: Towards the plateau of productivity. (March 2022) - Stöcker, Claudia; Bennett, Rohan; Koeva, Mila; Nex, Francesco; Zevenbergen, Jaap
Abstract: Unmanned aerial vehicles (UAVs) are considered an innovative tool for land administration. However, despite the prospects and market opportunities in the domain, there is a gap between experimentation and widespread technology diffusion. In this work, the Framework for Effective Land Administration (FELA) and the Hype Cycle concept are integrated to understand the dynamics of the innovation process of UAVs for the land administration sector. Empirical data stems from literature and interviews of UAV and land administration experts worldwide. The majority of experts estimate UAV technology to be in a phase in which the innovation needs to overcome initial unmet expectations to foster market development and increased adoption. The assessment indicates the changing importance of different FELA pathways during this process. Enabling laws and policies and supporting governance, accountability and institutions are crucial to create such a UAV-friendly national ecosystem early on and allay exaggerated expectations. Once this ecosystem has been made, market demand is expected to surge driven by partnerships, adapted standards, tech advocacy and awareness-raising campaigns, highlighting the superiority of high-resolution data amongst other benefits of UAV technology. These insights can be used as a baseline to direct national strategic decisions towards the increased adoption of UAVs in land administration. Highlights: The Framework for Effective Land Administration (FELA) and the Hype Cycle are fused to establish an analytical framework. We identify alternating top-down and bottom-up dynamics impacting the diffusion of UAVs. FELA can be seen as a set of levers that can be utilised or calibrated differently to support innovation. Our research provides a baseline to direct national strategic decisions to scale up the use of UAVs in land administration.